Store Atmosphere Dominates Impulse Buying in Modern Retail: Suasana Toko Mempengaruhi Pembelian Impulsif dalam Ritel Modern - Muhammad Irfan Ramadhan; Lia Nirawati (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Modern retail competition increasingly emphasizes in-store factors that shape consumer purchasing behavior, particularly unplanned purchases. Specific Background Within the Indonesian modern retail context, Miniso at Tunjungan Plaza Surabaya represents a physical retail setting where product quality, product display, and store atmosphere are deliberately managed to attract consumers. Knowledge Gap Prior studies frequently examine these variables separately or in different retail contexts, leaving limited integrated empirical evidence within a single modern retail model. Aims This study aims to analyze the relationships between product quality, product display, and store atmosphere with impulse buying among Miniso consumers at Tunjungan Plaza Surabaya, both partially and simultaneously. Results Using a quantitative associative design and multiple linear regression analysis of 100 respondents, the findings show that product quality, product display, and store atmosphere are all positively and significantly associated with impulse buying, with store atmosphere demonstrating the strongest contribution. Novelty The study offers an integrated examination of three key retail stimuli within one analytical model applied to a modern specialty retailer in a high-traffic shopping mall. Implications These findings suggest that coordinated management of product attributes, visual merchandising, and physical store environment is central to understanding impulse buying behavior in modern retail settings. Highlights: Physical retail environment shows the strongest statistical contribution to unplanned purchasing behavior. Visual merchandising and merchandise attributes jointly relate to spontaneous consumer decisions. An integrated retail stimulus model explains a substantial proportion of purchasing variability. Keywords: Product Quality, Display Product, Store Atmosphere, Impulse Buying, Ritel Modern